2017
DOI: 10.1097/aud.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Deafness Alters Sensory Weighting for Postural Control

Abstract: This increased somatosensory reliance may increase postural sway when it comes to more challenging postural conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…Anterior-posterior postural sway increased with sensory perturbations similarly in both environments. This is probably because the visual perturbation in both environments was in the anterior-posterior plane (flow of people or stars), and so a greater response in this direction is expected with an increased visual weight ( 51 ). As expected, further insights into people's motor behavior can be obtained from the head segment.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior-posterior postural sway increased with sensory perturbations similarly in both environments. This is probably because the visual perturbation in both environments was in the anterior-posterior plane (flow of people or stars), and so a greater response in this direction is expected with an increased visual weight ( 51 ). As expected, further insights into people's motor behavior can be obtained from the head segment.…”
Section: Discussionmentioning
confidence: 99%
“…The vestibular system is, of course, just one source of information contributing to balance control, alongside visual, somatosensory, and even auditory input [22, 23]. Various studies have considered disorders of postural stability in patients with hearing loss, as well as the impact of cochlear implantation on postural stability [10, 19, 24]. However, the majority of falls occur during ambulation, not static stance, and a key factor in preventing falls is the ability to quickly take an appropriate recovery step.…”
Section: Introductionmentioning
confidence: 99%
“…Auditory input has an impact on postural control and balance (e.g., Houde et al, 2016 ; Maheu et al, 2017a , b , 2019 ). It has been suggested that the auditory input can be used to compensate for vestibular loss (e.g., Maheu et al, 2019 ), which is a common problem among older adults ( Baloh et al, 2001 ).…”
Section: Impact On Posture and Balancementioning
confidence: 99%